Extraction and Preliminary Analysis of Aloin Obtained from Aloe barbadensis Miller - Nagaraju, M.; Ramulla, Suhas; Murthy, N.Y.S. (Asian Journal of Chemistry, 2011)
Extraction of aloin from the plant Aloe barbadensis Miller has been accomplished by a sequence of steps. Preliminary investigations like TLC, UV-Vis assay, nitrogen content, moisture content, ash content were carried out. The results are tabulated and a comparison of the results obtained with soil grown plant and in vitro cultured plant were also presented.